Assessment and detection of the potential contaminants from oil palm empty fruit bunch fiber-based biodegradable tray - Mat Ariffin, Naziruddin; Jawaid, Mohammad; Yusof, Noor Liyana; Abdul Mutalib, Noor Azira; Ahmad, M. F.; Sanny, Maimunah; Alzahari, Amir (Elsevier, 2021)
The advent of food contact material made from oil palm empty fruit bunch (EFB) fiber serves as a biodegradable alternative to petrochemical-based materials. This material needs to be tested according to strict regulations for its compliance as a food contact material. Present work aims to determine the presence of chemical contaminants in the EFB tray as compared to commercially available bagasse fiber-based tray and recycled Kraft fiber-based tray. The chemical contaminants were detected, and their levels were compared to the established limits. Gas Chromatography-Electron Capture Detector (GC-ECD) was used to detect and quantify Polychlorinated Biphenyls’ (PCBs) presence in all fiber-based trays. Meanwhile, the presence of phthalates, benzophenone, and 4-methylbenzophenone was quantified by means of Gas Chromatography-Mass Spectrometry (GC–MS). The levels of mercury in fiber-based trays was measured by Atomic Absorption Spectroscopy (AAS) and the levels of lead and cadmium was measured by Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES). Additionally, formaldehyde migrated to aqueous extracts from fiber-based trays at two conditions (cold and hot) was determined by an ultraviolet-visible (UV–vis) spectroscopy. Each fiber-based tray exhibited different innate chemical contaminants. Fortunately, most of the contaminants identified in the EFB fiber-based tray were found at trace levels. Unexpectedly, the migrated formaldehyde level found in hot water extract of recycled Kraft fiber-based tray was the highest and exceeds the limit set in Commission Regulation (EU) No 10/2011, which is at 15 mg/kg of simulant. The results implied that the EFB fiber-based tray was inert and suitable for its application as food contact material.